SYSTEMATIC LITERATURE REVIEW (SLR): NUCLEAR POWER PLANTS - Muhammad Reza Maulana Aliva; Nofi Yendri Sudiar; Hamdi Hamdi (JURNAL TEKNOLOGI REAKTOR NUKLIR TRI DASA MEGA, 2023)
Nuclear Power Plant (NPP) is a thermal power plant using one or several nuclear reactors as its heat source. NPP uses radioactive materials such as uranium as the heat source by utilizing fission reactions. The fission reaction produces enormous heat energy. Currently, there are many studies on NPPs, ranging from technological developments to the environmental impact of the NPP itself. This study aims to identify research developments on nuclear power plants from around the world obtained from relevant international journals in 2017-2023. The method used in this study is the Systematic Literature Review (SLR) method. The SLR method is used to identify, review, evaluate, and conclude all available research with interesting topic areas, with specific relevant research questions. Data were obtained by searching journals with Harzing's Publish or Perish application from the Scopus journal database. There are 191 journals with the keyword " Nuclear Power Plant " obtained from the Scopus database. Then these journals are filtered by type of article and if the number of citations is more than 32, then 49 articles are obtained which will be reviewed. This SLR method shows the development of research on NPP in several developed countries that have been using this technology for a long time. In addition, research topics such as the Fukushima accident, fault diagnostics, and safety assessment are the most discussed topics in the research so that they can be used as a reference for countries that are developing NPP.